Legal and Human Resource Frameworks for Autonomous Vessel Operations: Regulatory Compliance and Seafarer Workforce Transition in Indonesian Archipelagic Waters - Tata Heru Prabawa (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
This research investigates integrated legal-human resource frameworks for autonomous vessel operations in Indonesian archipelagic waters, addressing regulatory compliance gaps and seafarer workforce transition challenges. Through qualitative analysis involving 38 stakeholders including maritime lawyers, regulatory officials, ship operators, seafarer unions, training institutions, and autonomous technology developers, this study examines how existing maritime legal frameworks prove inadequate for unmanned operations while workforce displacement threatens 150,000+ Indonesian maritime workers. Results demonstrate that successful autonomous vessel adoption requires coordinated legal-HR approaches addressing liability allocation (achieving 75-85% clarity through multi-party frameworks), competency certification for remote operators (reducing training gaps by 60-70%), career transition pathways (enabling 55-65% workforce adaptation), and regulatory harmonization (improving compliance efficiency by 45-60%). Key barriers include UNCLOS Article 94 incompatibility, insurance unavailability, seafarer resistance, and jurisdictional fragmentation. Findings reveal that archipelagic contexts demand unique legal-HR solutions integrating traditional maritime rights, hybrid operational modes, and just transition principles. This research contributes frameworks enabling Indonesia to proactively shape autonomous vessel regulations protecting both technological innovation and maritime workforce interests during critical technology transition.